A continuously pumped reservoir of ultracold atoms. (8th July 2015) - Mahnke, J; Kruse, I; Hüper, A; Jöllenbeck, S; Ertmer, W; Arlt, J; Klempt, C
Abstract: Typical sources of ultracold atoms operate with a considerable delay between the delivery of ensembles due to sequential trapping and cooling schemes. Therefore, alternative schemes for the continuous generation of ultracold atoms are highly desirable. Here, we demonstrate the continuous loading of a magnetic trap from a quasi-continuous atom beam. We achieve a steady state with magnetically trapped atoms and a temperature of K. The ensemble is protected from laser light sources, a requirement for its application in metrological tasks or sympathetic cooling. The continuous scheme is robust and applicable to a wide range of particles and trapping potentials.